Subsidence monitoring of offshore platforms in Malaysian waters using GPS technique - Othman, Rusli; Setan, Halim (2005)

(untitled)
Between the east coast of Malaysia Peninsula and the west coast of Sabah and Sarawak lies South China Sea, which locate more than a hundred of offshore platforms, which extract oil and gas for major oil production companies such as PETRONAS and SHELL. One of the major problems of these platforms is the occurrence of subsidence, which may cause disaster to man and platform itself. Since these offshore platforms are located hundreds of kilometers from shore, the GPS technique is seemed the only possible method that is able to carry out subsidence monitoring for geodetic method. This paper will look at the potential of GPS technique for monitoring of subsidence of these platforms in Malaysian waters. The existence of MASS stations in Peninsular Malaysia and in Sabah and Sarawak that continuously logging in data throughout the years give an option for carrying out subsidence monitoring of offshore platforms. The Bernese GPS Software is used in the processing of these GPS data and the output will then use for the detection of subsidence of these offshore platforms. This paper will also discuss the strategy of data processing and subsidence detection of the offshore platforms located in the Malaysian waters.